Ke-ummi-an Rasulullah dan Korelasinya Terhadap Keautentikan Al-Qur’an - Waskito, Subarkah Yudi; Astuti, Nurhaliza Yuki (Izzatuna: Jurnal Ilmu Al-Qur'an dan Tafsir, 2021)
The Qur'an that Allah revealed to the Prophet Muhammad is a great miracle and proof of the greatness of Allah towards all of His creation. The ability of the Qur'an to survive to this day from various forms of misuse of meaning and lafadz is proof of the authenticity and divinity of its source. However, until now accusations related to the authenticity of the Qur'an or the divinity of its source, are still being raised by orientalists. This paper intends to examine the authenticity of the Qur'an in terms of the ummi of the Messenger of Allah, so that people are protected from slander spread by orientalists, or misunderstandings in interpreting the word ummi which is leaned on the Prophet, given the differences of opinion regarding the meaning of ummi. the method used by the author is library research or literature review, namely by deepening sources related to the research theme. The results of the study show that the authenticity of the Qur'an will always be guaranteed until the Day of Judgment, and no one will ever be able to match it, while the meaning of ummi which is relied on the Messenger of Allah means that the Prophet is unable to read and write, and the Ummi of the Prophet is not a lack but a miracle and glory so that the accusation that the Qur'an is the result of his study of the previous books can be dispelled.